Effects of ohmic heating on the immunoreactivity of β-lactoglobulin – a relationship towards structural aspects. Issue 5 (22nd April 2020) - Pereira, Ricardo N.; Costa, Joana; Rodrigues, Rui M.; Villa, Caterina; Machado, Luís; Mafra, Isabel; Vicente, António
Abstract : Ohmic heating changes the immunoreactivity of monomeric and aggregated β-LG forms. Abstract : β-Lactoglobulin (β-LG) encompasses important biological functions, but it is also a major milk allergen, being responsible for the high incidence of cow's milk allergy in childhood. Despite numerous studies addressing the effect of thermal processing on the immunoreactivity of β-LG, little is known about the impact of emergent food processing technologies, such as ohmic heating (OH), on its immunoreactivity. This study describes, for the first time, the effects of thermal and electric effects of OH on the immunoreactivity of β-LG. The influence of high-temperature short time (HTST; 72.5 °C for 15 and 90 °C for 1 s) and low-temperature long time (LTLT; 65 °C for 30 min) pasteurization binomials combined with different electrical variables (electric field intensity and electrical frequency) was evaluated and compared with that of conventional heating. HTST at 90 °C for 1 s extensively affects the protein secondary structure and increases the levels of reactive aggregates, resulting in increased total immunoreactivity (assessed by ELISA and immunoblotting). OH at 4 V cm −1 and a frequency of 25 kHz reduced the immunoreactivity of monomeric β-LG and its resultant aggregates, compared with conventional heat treatments. In contrast, the presence of electric fields (4 V cm −1 and 25 kHz) during LTLT increased the immunoreactivity of monomeric β-LG. The thermal and electrical variables of OH change the balance between monomeric and aggregated forms of β-LG, affecting their ability to bind specific antibodies. These outcomes bring novel insights into how to modulate OH aiming at reducing the allergenic potential of β-LG based products.